Crime and punishment perspectives from the humanities - Sarat, Austin (Studies in law, politics, and society, 2005)
Volume 37 of "Studies in Law, Politics, and Society" presents a special issue devoted to exploring humanistic perspectives on the subject of punishment. Drawing together a distinguished group of interdisciplinary scholars, it explores the way "deviant" subjects are constructed and made available for punishment, the philosophical context within which decisions about punishment are made, and the inner workings of the penal apparatus. Diverse in their theoretical inspirations and approaches, the articles published here represent a significant advance in our understanding of the complex intersections of punishment, politics, and culture.